Didelio meistriškumo futbolo komandos metinio treniruotes ciklo raidos analize - Adambekov, Y.; Iljasova, A.; Achmetova, E.; Adambekov, K. (Sporto Mokslas-Sport Science, 2015)
Long-term observation of high performance football teams training has shown that training for championships under the system of two macro-cycles has its own characteristics in the planning of educational-training process in the context of annual training cycle. However, in each country and, especially in Kazakhstan, it has its own specific conditions as well. The aim of the present study was based on experiment to study and compare the structure and content of the training process of football major league teams in different variants of the annual training cycle formation.